Understanding the Gut-Kidney Axis in Antineutrophil Cytoplasmic Antibody-Associated Vasculitis: An Analysis of Gut Microbiota Composition - Yu, Meilian; Li, Lingzhi; Ren, Qian; Feng, Han; Tao, Sibei; Cheng, Lu; Ma, Liang; Gou, Shen-Ju; Fu, Ping (Frontiers in Pharmacology, 2022)
Increasing evidence suggested that gut microbiota played critical roles in developing autoimmune diseases. This study investigated the correlation between gut microbiota and antineutrophil cytoplasmic antibody-associated vasculitis (AAV) with kidney injury. We analyzed the fecal samples of 23 AAV patients with kidney injury using a 16s RNA microbial profiling approach. The alpha-diversity indexes were significantly lower in AAV patients with kidney injury than healthy controls (Sobs P < 0.001, Shannon P < 0.001, Chao P < 0.001). The beta-diversity difference demonstrated a significant difference among AAV patients with kidney injury, patients with lupus nephritis (LN), and health controls (ANOSIM, p = 0.001). Among these AAV patients, the Deltaproteobacteria, unclassified_o_Bacteroidales, Prevotellaceae, Desulfovibrionaceae Paraprevotella, and Lachnospiraceae_NK4A136_group were correlated negatively with serum creatinine, and the proportion of Deltaproteobacteria, unclassified_o_Bacteroidales, Desulfovibrionaceae, Paraprevotella, and Lachnospiraceae_NK4A136_group had a positive correlation with eGFR. In conclusion, the richness and diversity of gut microbiota were reduced in AAV patients with kidney injury, and the alteration of gut microbiota might be related with the severity of kidney injury of AAV patients. Targeted regulation of gut microbiota disorder might be a potential treatment for AAV patients with kidney injury.